1997
DOI: 10.1002/hep.510250129
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Hemochromatosis–Associated Alleles Is Increased in British Patients With Sporadic Porphyria Cutanea Tarda

Abstract: of the hemochromatosis-linked HLA allele, HLA-A3, and The cause of the hepatic siderosis and iron overload PCT 7-9 but not by others. [10][11][12][13] Recently it has been shown that that is common in porphyria cutanea tarda (PCT) is unthe hemochromatosis gene (HFE) is most likely located close certain. Heterozygosity for genetic hemochromatosis to the microsatellite DNA marker, D6S1260 (formerly CS5), has been supported by some studies of the association which is 700kb telomeric to the marker D6S105, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…This is in contrast to reports of populations of European descent, including Britains, Dutchmen, Americans, Australians, and South Africans. [8][9][10][11][12][13] However, our findings are in accordance with reports from the Italian population recently published by Sampietro et al 6 who also found no association between the C282Y mutation and SPCT. The H63D mutation was observed in 10 of the 48 PCT patients corresponding to 20.8%.…”
Section: C282y and H63d Mutations In The Hfe Gene Are Not Associatedsupporting
confidence: 93%
“…This is in contrast to reports of populations of European descent, including Britains, Dutchmen, Americans, Australians, and South Africans. [8][9][10][11][12][13] However, our findings are in accordance with reports from the Italian population recently published by Sampietro et al 6 who also found no association between the C282Y mutation and SPCT. The H63D mutation was observed in 10 of the 48 PCT patients corresponding to 20.8%.…”
Section: C282y and H63d Mutations In The Hfe Gene Are Not Associatedsupporting
confidence: 93%
“…19 The C282Y mutation, which is found in 6% to 11% of the U.K. population, 18,20 is in complete linkage disequilibrium with the H63D mutation. The H63D mutation is found in 16% to 25% of the population, 21 but its role, if any in HH, is controversial. It seems to be associated with hemochromatosis only when inherited together with the C282Y mutation.…”
mentioning
confidence: 99%
“…A liver-specific process that causes clinically overt PCT in response to hepatitis viral infection might be caused by interactions between genes that control the level of URO-D in the cells and genes of which the expression induces the inactivation of the protein. In this manner, Roberts et al 30,33 have shown that hemochromatosisassociated alleles were more frequently carried by British patients with s-PCT than by the general population. Different alleles of other modulatory genes of URO-D could be related to a more or less pronounced sensitivity to viral infection in s-PCT patients.…”
Section: Discussionmentioning
confidence: 92%
“…Iron participates in the generation of reactive oxygen species and in the oxidation of uroporphyrinogen to uroporphyrin, 28,29 contributing to the development of the hepatic lesions. A recent study reveals that inheritance of one or more hemochromatosis mutant alleles is an important susceptibility factor for the development of s-PCT [30][31][32][33] in some countries.…”
Section: Discussionmentioning
confidence: 99%